PRIORITY TASKS AND WAYS TO SOLVE THEM IN ENSURING EMPLOYMENT OF THE POPULATION IN UZBEKISTAN - Odina Teshabaeva; Mashxurbek Qosimov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article is about the ways and mechanisms of increasing the competitiveness of family entrepreneurship in our country, developing this industry in ensuring employment of the population and increasing the level of using its economic potential.